(untitled) (TEST Antologia di Diritto Pubblico, 2025)
The contribution is dedicated to the Vittorio Emanuele Orlando’s legal theory of political representation, as presented in the essay De la nature juridique de la représentation politique, published in the Revue de Droit Public et de la Science Politique in 1895. In this perspective, the essay analyzes the main passages through which the critique of the theory of the political mandate and the principle of popular sovereignty is developed by Orlando; in doing so, the paper dwells on his conception of the political representation - intended as an act of designation - by investigating its relationship with the legal doctrine of the 19th and 20th centuries and, then, by highlighting its limits in front of the democratic principle claimed by the Italian Constitution.